DISTINCTIVE FEATURES OF A FETUS DEVELOPING IN THE WOMB - Ergasheva Malika Alimardonovna; Kholmamatova Feruza Olim qizi (Web of Journals Publishing, 2025)
This article is about how a fetus spends its final weeks in the womb, and what changes first-time mothers should be prepared for during this period. Of course, all stages of pregnancy are extremely important and require attention. A lot has to happen for a fetus to form, grow, and be born. Learning about how a fetus grows can be exciting and eye-opening, especially when you realize how many organs, systems, and body functions develop over the course of nine months. It is important to note that any changes in the fetus during pregnancy should not be ignored.
Keywords: Motility, fetal head size, cerebral circulation, fetal heart.